On the characteristics of head on collision of dust ion acoustic solitons in the adiabatic dusty plasmas - M.A.H. Khaled (Journal of King Saud University: Science, 2014)
Based on a one-dimensional mode, the characteristics of the head on collision between two dust ion acoustic solitons (DIASs), propagating in opposite directions in adiabatic dusty plasmas composed of adiabatic non-inertial electrons, adiabatic inertial ions and immersed (negatively/positively) charged dust grains have been investigated. The extended Poincaré–Lighthill–Kuo (PLK) method has been used to obtain two side Korteweg-de Vries (KdV) equations for DIASs. The analytical phase shifts and trajectories after collision of two solitons are given. The effects of adiabaticity of electron and ion fluids, concentration of negatively/positively charged static dust particles and ion temperature to electron temperature ratio on the phase shift are studied. It is found that these factors significantly affect the phase shifts.